Angular spectrum representation of the Bessel-Gauss beam and its approximation: A comparison with the localized approximation. (July 2022) - Shen, Jianqi; Wang, Ying; Yu, Haitao; Ambrosio, Leonardo André; Gouesbet, Gérard
Highlights: Angular spectrum representation of the Bessel-Gauss beam is introduced into the quadrature method of the GLMT. The connection between the ASD method and the GLMT quadrature method is studied. The ASD-BSCs are approximated under the paraxial condition to the BSCs obtained in localized approximations. Angular spectrum of the beam is used for validating the LA method. Abstract: The angular spectrum representation of the vector Bessel-Gauss beam is used for discussing the connection between the angular spectrum decomposition (ASD) method and the quadrature method of the generalized Lorenz-Mie theory (GLMT). Under the paraxial condition, the beam shape coefficients (BSCs) obtained in the ASD method can be approximated to the same expressions as those obtained in the localized approximation method. The validity of the approximate method for evaluating the BSCs is numerically studied, based on both the beam's angular spectrum and the off-axis distance.